Neuroscience in HR : Employee Behavior Analysis to Optimize Performance - Sumiati Sumiati (Institut Teknologi dan Bisnis (ITB) Semarang, 2025)
This study aims to analyze the effect of work motivation, neuroscience factors, emotional intelligence, and job type on employee performance. This research uses quantitative methods with multiple linear regression approaches. Data was collected from 100 respondents who work in various industrial sectors. The results showed that emotional intelligence and work motivation have a significant influence on employee performance, while neuroscience factors and job type did not show a significant influence. The F-test yields a value of 21,795 with a significance of 0.000, which indicates that simultaneously, the independent variables in this model have a significant effect on employee performance. The R-Square value of 0.479 indicates that 47.9% of the variation in employee performance can be explained by the variables used in the model, while 52.1% is explained by other factors outside this model. The results of this study indicate that companies need to improve employees' work motivation and emotional intelligence to optimize their performance. In addition, this study recommends exploring additional variables that may affect employee performance to improve the accuracy of the prediction model.